The Supply of Child Labour - Alessandro Cigno (Institute for the Study of Labor (IZA), 2004)
The paper develops a theoretical framework, and a diagrammatic apparatus, for explaining the supply of child labour. It examines the effect of credit, insurance, and poverty (defined as more than just low income). It also explains bonded child labour, a modern form of slavery closely associated with the worst forms of child exploitation. The analysis is positive, but provides some of the elements for a normative judgement.
Keywords: J24; D13; O12; J82; J22; J13; I12; 330; child labour; bonded labour; education; health; credit; insurance; poverty; Kinderarbeit; Arbeitsangebot; Haushaltsökonomik; Armut; Theorie; bonded labor